Efektivitas Antibiotik Benzoil Peroksida Terhadap Bakteri Propionibacterium Acnes Dengan Metode Difusi Pada Pasien Acne Vulgaris - Kayla Rahma Mulqi; Eka Silvia; Ismalia Husna; M. Syafei Hamzah (CV. Jasa Sukses Abadi, 2022)
Acne vulgaris is a disorder limited to the visible pilosebaceous unit. Acne presents with a pleomorphic arrangement. lesions consisting of comedones, papules, pustules, and nodules of varying extent and severity. While the course of acne may be self-limiting, the sequelae can be lifelong, with scar formation that is difficult to go away. Benzoyl peroxide is an effective topical agent for the treatment of acne vulgaris. The way it works can penetrate the stratum corneum or follicular openings unchanged and is converted metabolically to benzoic acid in the epidermis and dermis. Approximately 5% of the applied dose is absorbed from the skin in an 8 hour period. It has been postulated that the mechanism of action of benzoyl peroxide in acne is related to its antimicrobial activity against P. acnes and to its exfoliating and comedolytic effects.